Polycarbonate resin composition

The polycarbonate resin composition, featuring graphite with specific aspect ratio and particle size, addresses the challenge of achieving high dielectric constant and low dielectric loss tangent while maintaining impact resistance and flowability, making it suitable for diverse applications.

JP2025044913APending Publication Date: 2025-04-02MITSUBISHI CHEM CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023152740
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-04-02

AI Technical Summary

Technical Problem

Existing polycarbonate resin compositions face challenges in achieving a high dielectric constant of 4.5 or more and less than 6.5, while maintaining a low dielectric loss tangent, excellent impact resistance, and good flowability.

Method used

A polycarbonate resin composition containing 3.0 to 6.0 parts by mass of graphite with an aspect ratio greater than 20 and a particle diameter of 300 μm or less, which achieves the desired dielectric properties and mechanical performance.

Benefits of technology

The composition exhibits a high dielectric constant, low dielectric loss tangent, and excellent impact resistance and flowability, making it suitable for various electronic and automotive applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044913000001
    Figure 2025044913000001
  • Figure 2025044913000002
    Figure 2025044913000002
  • Figure 2025044913000003
    Figure 2025044913000003
Patent Text Reader

Abstract

To provide a polycarbonate resin composition having a high dielectric constant and low dielectric dissipation factor, as well as superior flowability (moldability) and impact resistance.SOLUTION: A polycarbonate resin composition comprises, relative to 100 pts.mass of polycarbonate resin (A), 3.0 to 6.0 pts.mass of graphite (B) having an aspect ratio of more than 20 and a particle diameter of 300 μm or less, and exhibits a relative dielectric constant of 4.5 or more and less than 6.5 at a frequency of 5.8 GHz.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polycarbonate resin composition, and more particularly to a polycarbonate resin composition having a high dielectric constant, a low dielectric tangent, and excellent fluidity and impact resistance. [Background technology]

[0002] Polycarbonate resin has excellent mechanical strength, heat resistance, transparency, electrical properties, etc., and is therefore widely used in many applications, including various optical parts, electrical and electronic equipment parts, automotive interior and exterior parts, office equipment parts, sheets, machine parts, and building materials, and has recently been widely used in the fields of automotive parts, office equipment, electrical and electronic equipment, and communication equipment.

[0003] For example, various in-vehicle touch panels and touch sensors require improved touch sensitivity to meet the demand for high performance, and polycarbonate resin materials with high dielectric constants are required. In recent years, technological advances in areas such as high-speed communication have been remarkable, and next-generation communication methods that use high-frequency radio waves (such as 5G) require materials with specific dielectric constants.

[0004] It is known that various additives are blended to adjust the dielectric constant of polycarbonate resin, etc. For example, Patent Document 1 proposes a polycarbonate resin composition containing barium titanate with an average sphericity of 0.86 or more. Although barium titanate can increase the dielectric constant, it is a special material and tends to have poor moldability. 2. Description of the Related Art In order to impart thermal conductivity or electrical conductivity to resin materials, it is common practice to blend carbon materials such as graphite, carbon black, or carbon fibers. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent Publication No. 2021-066831 Summary of the Invention [Problem to be solved by the invention]

[0006] However, it is difficult to control the dielectric constant with carbon fibers, and the dielectric loss tangent is likely to deteriorate. Carbon black is difficult to handle, and requires a large amount of addition, which has the problem of deteriorating fluidity (moldability). It is thought that the dielectric constant can be increased by blending graphite, but blending a large amount of graphite is likely to impair impact resistance, and there is also the problem that it is difficult to control the dielectric constant and dielectric loss tangent. The object (object) of the present invention is to provide a polycarbonate resin composition that has a high dielectric constant of 4.5 or more and less than 6.5, a low dielectric loss tangent, and excellent impact resistance and fluidity (moldability). [Means for solving the problem]

[0007] As a result of intensive research aimed at achieving the above object, the present inventors have discovered that a polycarbonate resin composition incorporating a small amount of graphite having a specific aspect ratio and a specific particle size exhibits a high dielectric constant of 4.5 or more and less than 6.5 at a frequency of 5.8 GHz, a low dielectric tangent, and excellent fluidity and impact resistance, thereby completing the present invention. The present invention relates to the following polycarbonate resin composition.

[0008] 1. A polycarbonate resin composition comprising 100 parts by mass of polycarbonate resin (A) and 3.0 to 6.0 parts by mass of graphite (B) having an aspect ratio of more than 20 and a particle size of 300 μm or less, and having a relative dielectric constant of 4.5 or more and less than 6.5 at a frequency of 5.8 GHz. 2. The polycarbonate resin composition according to the above item 1, wherein a molded article of the resin composition has a thermal conductivity in the resin flow direction (MD) of 0.7 w / m·k or less. 3. The polycarbonate resin composition according to the above 1 or 2, wherein the content of the carbon fiber is 0 to 0.5 parts by mass per 100 parts by mass of the polycarbonate resin (A). 4. The polycarbonate resin composition according to 1 or 2 above, wherein the content of the laser direct structuring additive is 0 part by mass or more and less than 0.5 part by mass per 100 parts by mass of the polycarbonate resin (A). 5. A molded article formed from the polycarbonate resin composition according to any one of 1 to 4 above. Effect of the Invention

[0009] The polycarbonate resin composition of the present invention has a high dielectric constant and a low dielectric tangent, and is also excellent in flowability and impact resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will now be described in further detail. In this specification, unless otherwise specified, the symbol "to" is used to mean that the numerical values ​​before and after it are included as the lower limit and upper limit.

[0011] The polycarbonate resin composition of the present invention is characterized in that it contains 3.0 to 6.0 parts by mass of graphite (B) having an aspect ratio of more than 20 and a particle size of 300 μm or less per 100 parts by mass of polycarbonate resin (A), and has a relative dielectric constant of 4.5 or more and less than 6.5 at a frequency of 5.8 GHz.

[0012] [Polycarbonate resin (A)] The polycarbonate resin (A) used in the present invention is not particularly limited, and various types can be used. Polycarbonate resins can be classified into aromatic polycarbonate resins in which the carbons directly bonded to the carbonate bonds are aromatic carbons, and aliphatic polycarbonate resins in which the carbons directly bonded to the carbonate bonds are aliphatic carbons, and either type can be used. Among them, aromatic polycarbonate resins are preferred as the polycarbonate resin (A) from the viewpoints of heat resistance, mechanical properties, electrical properties, etc.

[0013] Among the monomers that are raw materials for aromatic polycarbonate resins, examples of aromatic dihydroxy compounds include: Dihydroxybenzenes such as 1,2-dihydroxybenzene, 1,3-dihydroxybenzene (i.e., resorcinol), and 1,4-dihydroxybenzene; Dihydroxybiphenyls such as 2,5-dihydroxybiphenyl, 2,2'-dihydroxybiphenyl, and 4,4'-dihydroxybiphenyl;

[0014] dihydroxynaphthalenes such as 2,2'-dihydroxy-1,1'-binaphthyl, 1,2-dihydroxynaphthalene, 1,3-dihydroxynaphthalene, 2,3-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, 1,7-dihydroxynaphthalene, and 2,7-dihydroxynaphthalene;

[0015] dihydroxydiaryl ethers such as 2,2'-dihydroxydiphenyl ether, 3,3'-dihydroxydiphenyl ether, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether, 1,4-bis(3-hydroxyphenoxy)benzene, and 1,3-bis(4-hydroxyphenoxy)benzene;

[0016] 2,2-bis(4-hydroxyphenyl)propane (i.e., bisphenol A), 1,1-bis(4-hydroxyphenyl)propane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane (i.e., bisphenol C), 2,2-bis(3-methoxy-4-hydroxyphenyl)propane, 2-(4-hydroxyphenyl)-2-(3-methoxy-4-hydroxyphenyl)propane, 1,1-bis(3-tert-butyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 2-(4-hydroxyphenyl)-2-(3-cyclohexyl-4-hydroxyphenyl)propane, α,α'-bis(4-hydroxyphenyl)-1,4-diisopropylbenzene, 1,3-bis[2-(4-hydroxyphenyl)-2-propyl]benzene, bis(4-hydroxyphenyl)methane, Bis(4-hydroxyphenyl)cyclohexylmethane, Bis(4-hydroxyphenyl)phenylmethane, Bis(4-hydroxyphenyl)(4-propenylphenyl)methane, Bis(4-hydroxyphenyl)diphenylmethane, Bis(4-hydroxyphenyl)naphthylmethane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 1,1-bis(4-hydroxyphenyl)-1-naphthylethan, 1,1-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)pentane, 1,1-bis(4-hydroxyphenyl)hexane, 2,2-bis(4-hydroxyphenyl)hexane, 1,1-bis(4-hydroxyphenyl)octane, 2,2-bis(4-hydroxyphenyl)octane, 4,4-bis(4-hydroxyphenyl)heptane, 2,2-bis(4-hydroxyphenyl)nonane, 1,1-bis(4-hydroxyphenyl)decane, 1,1-bis(4-hydroxyphenyl)dodecane, Bis(hydroxyaryl)alkanes such as;

[0017] 1,1-bis(4-hydroxyphenyl)cyclopentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3-dimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3,4-dimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3,5-dimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxy-3,5-dimethylphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3-propyl-5-methylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3-tert-butyl-cyclohexane, 1,1-bis(4-hydroxyphenyl)-4-tert-butyl-cyclohexane, 1,1-bis(4-hydroxyphenyl)-3-phenylcyclohexane, 1,1-bis(4-hydroxyphenyl)-4-phenylcyclohexane, Bis(hydroxyaryl)cycloalkanes such as;

[0018] 9,9-bis(4-hydroxyphenyl)fluorene, Cardo structure-containing bisphenols such as 9,9-bis(4-hydroxy-3-methylphenyl)fluorene;

[0019] 4,4'-dihydroxydiphenyl sulfide, Dihydroxydiaryl sulfides such as 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide; Dihydroxydiaryl sulfoxides such as 4,4'-dihydroxydiphenyl sulfoxide and 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide; 4,4'-dihydroxydiphenyl sulfone, dihydroxydiarylsulfones such as 4,4'-dihydroxy-3,3'-dimethyldiphenylsulfone; etc.

[0020] Of these, bis(hydroxyaryl)alkanes are preferred, and bis(4-hydroxyphenyl)alkanes are particularly preferred. In particular, from the standpoint of impact resistance and heat resistance, 2,2-bis(4-hydroxyphenyl)propane (i.e., bisphenol A) and 2,2-bis(3-methyl-4-hydroxyphenyl)propane (i.e., bisphenol C) are preferred. The aromatic dihydroxy compounds may be used alone or in any combination of two or more in any ratio.

[0021] Among the monomers that are raw materials for polycarbonate resins, examples of carbonate precursors include carbonyl halides, carbonate esters, etc. The carbonate precursors may be used alone or in any combination and ratio of two or more.

[0022] Specific examples of carbonyl halides include phosgene; haloformates such as bischloroformates of dihydroxy compounds and monochloroformates of dihydroxy compounds; and the like.

[0023] Specific examples of carbonate esters include diaryl carbonates such as diphenyl carbonate and ditolyl carbonate; dialkyl carbonates such as dimethyl carbonate and diethyl carbonate; biscarbonates of dihydroxy compounds, monocarbonates of dihydroxy compounds, and carbonates of dihydroxy compounds such as cyclic carbonates.

[0024] The method for producing the polycarbonate resin (A) is not particularly limited, and any method can be adopted. Examples of the method include interfacial polymerization, melt transesterification, pyridine method, ring-opening polymerization of cyclic carbonate compounds, and solid-phase transesterification of prepolymers. Among these, the interfacial polymerization and melt transesterification methods are preferred because they have a higher effect of improving resistance to moist heat, and the interfacial polymerization method is particularly preferred.

[0025] The molecular weight of the polycarbonate resin (A) is preferably 10,000 to 50,000, more preferably 10,000 to 40,000, even more preferably 10,000 to 30,000, 10,000 to 26,000, and even more preferably 10,500 or more, 11,000 or more, particularly preferably 11,500 or more, most preferably 12,000 or more, and even more preferably 24,000 or less, particularly preferably 20,000 or less. By making the viscosity average molecular weight equal to or more than the lower limit of the above range, the mechanical strength of the polycarbonate resin composition of the present invention can be further improved, and by making the viscosity average molecular weight equal to or less than the upper limit of the above range, the decrease in the flowability of the polycarbonate resin composition of the present invention can be suppressed and improved, and the molding processability can be improved to facilitate molding process. Two or more kinds of polycarbonate resins having different viscosity average molecular weights may be mixed and used. In this case, polycarbonate resins having a viscosity average molecular weight outside the above-mentioned preferable range may be mixed.

[0026] The viscosity average molecular weight (Mv) is calculated by using methylene chloride as a solvent, measuring the intrinsic viscosity [η] (unit: dl / g) at 25°C using an Ubbelohde viscometer, and calculating the value according to the Schnell viscosity formula, i.e., η = 1.23 × 10 -4 Mv 0.83 The intrinsic viscosity [η] is the value calculated from the specific viscosity [η sp ] was measured and the value was calculated according to the following formula.

number

[0027] In order to improve the appearance and flowability of the molded article, the polycarbonate resin composition may contain a polycarbonate oligomer. The viscosity average molecular weight (Mv) of this polycarbonate oligomer is usually 1,500 or more, preferably 2,000 or more, and usually 9,500 or less, preferably 9,000 or less. Furthermore, the amount of the polycarbonate oligomer contained is preferably 30% by mass or less of the total amount of the polycarbonate resin and the polycarbonate oligomer.

[0028] Furthermore, the polycarbonate resin (A) may be not only a virgin raw material but also a polycarbonate resin regenerated from a used product (so-called material recycled polycarbonate resin), and it is preferable to contain both a virgin raw material and a recycled resin, or may be made of a recycled polycarbonate resin. The proportion of the recycled polycarbonate resin in the polycarbonate resin (A) may be, for example, 40% or more, 50% or more, 60% or more, 80% or more, or 100%.

[0029] Graphite The polycarbonate resin composition of the present invention contains graphite (B) having an aspect ratio of more than 20 and a particle size of 300 μm or less in a small amount of 3.0 to 6.0 parts by mass per 100 parts by mass of the polycarbonate resin (A). If the aspect ratio of graphite is 20 or less, the effect of improving the dielectric constant is small, and if the content is increased, the impact resistance and toughness (tensile strain) decrease. The larger the graphite particle size, the higher the dielectric effect at a low content, but the impact resistance and toughness decrease, so graphite particles of 300 μm or less are used.

[0030] The aspect ratio of the graphite is preferably at least 23, and more preferably at least 25. The aspect ratio of the graphite is preferably at most 60, more preferably at most 50, and even more preferably at most 45. If the aspect ratio is too large, it is not preferable because it leads to a decrease in mechanical strength and a significant anisotropy in molding shrinkage.

[0031] The particle size of the graphite is preferably 250 μm or less, more preferably 200 μm or less, even more preferably 150 μm or less, among which 100 μm or less, 80 μm or less, 70 μm or less, or 60 μm or less, and preferably 1 μm or more, among which 2 μm or more, 3 μm or less, 4 μm or more, and particularly preferably 5 μm or more. If the particle size is too small, the particles may become airborne during melt kneading, causing air pollution problems, or the melt viscosity of the resin composition may increase significantly, decreasing the flowability. However, if the average particle size is too large, poor supply such as bridging of the graphite-containing powder in a hopper during melt-kneading may occur, or the appearance of the molded product may be poor. Also, it is difficult to produce or obtain graphite with an excessively large average particle size.

[0032] The aspect ratio of graphite is the number average value of the ratio (major axis / minor axis) of the diameter of the longest part of graphite (major axis) to the shortest diameter (minor axis). The aspect ratio of graphite is obtained by randomly sampling (e.g., 50 particles) from an image obtained by observation with an electron microscope, determining the major axis / minor axis of each particle, and calculating the average value from the obtained measured values. The particle size of graphite is the number average particle size of the diameter (major axis) of the longest part of graphite, and is calculated from the obtained measured values ​​by measuring the major axis of graphite particles randomly sampled (e.g., 50 particles) from an image obtained by observation with an electron microscope. The average particle size is the average value of the particle size (here, the particle size refers to the diameter at the widest point between two parallel plates of graphite (the length of the gap between the plates)) measured for 100 samples in SEM (scanning electron microscope) observation. The aspect ratio of graphite is determined by measuring the thickness (here, thickness refers to the diameter (the length of the gap between the parallel plates) at the smallest position when the graphite is sandwiched between two parallel plates) of 100 samples under SEM (scanning electron microscope) observation, averaging the values ​​obtained, taking the average thickness as the average thickness, and calculating the ratio of average particle diameter / average thickness relative to the above-mentioned average particle diameter.

[0033] As the graphite (B), there is no limitation, and various graphites can be used as long as the aspect ratio is greater than 20 and the particle size is 300 μm or less. Graphite is also called graphite or graphite, and is a material composed of carbon with a hexagonal crystal structure. Either natural graphite or artificially produced graphite can be used. For example, flake graphite; artificial graphite obtained by heat-treating petroleum coke, petroleum pitch, amorphous carbon, or the like at high temperatures; expanded graphite (or expanded graphite) obtained by immersing such natural graphite or artificial graphite in a strong acid, further treating it with an oxidizing agent such as hydrogen peroxide or hydrochloric acid, and then washing it with water and rapidly heating it to expand it in the C-axis direction of the raw graphite; and the like can be used. These may be used alone or in combination of two or more kinds in any ratio.

[0034] It is also preferable that the graphite (B) is surface-treated to enhance dispersibility with polycarbonate resin, within the scope not impairing the effects of the present invention. Examples of such surface-treated graphite include graphite surface-treated with a surface treatment agent such as a silane coupling agent, a titanate coupling agent, or an aliphatic metal salt, graphite surface-treated with an ammonium salt or the like by an intercalation method, and graphite surface-treated with a resin such as a urethane resin or an epoxy resin as a binder.

[0035] The content of graphite (B) is 3.0 to 6.0 parts by mass relative to 100 parts by mass of polycarbonate resin (A) as described above. By including such a small amount of graphite (B), a polycarbonate resin composition can be obtained that exhibits a high dielectric constant, has a low dielectric tangent, has no anisotropy of dielectric properties, and is excellent in fluidity and impact resistance. If the content of graphite (B) is less than 3.0 parts by mass, the dielectric constant may be insufficient depending on the product. Also, if it exceeds 6.0 parts by mass, the impact resistance and fluidity tend to be insufficient, and the dielectric tangent tends to deteriorate. The content of graphite (B) is preferably 3.5 parts by mass or more, more preferably 5.5 parts by mass or less, so that the dielectric constant and dielectric tangent can be set to match the required performance of the product.

[0036] The polycarbonate resin composition of the present invention preferably contains 0 to 0.5 parts by mass of a carbon-based filler other than graphite (B) relative to 100 parts by mass of polycarbonate resin (A). More specifically, it is preferable that the composition does not substantially contain a carbon-based filler other than graphite (B). "Substantially free" means that the carbon-based filler is not contained, or the content of the carbon-based filler is 0.5 parts by mass or less relative to 100 parts by mass of polycarbonate resin (A) even if the carbon-based filler is contained. For example, the carbon fiber is preferably not contained, or the content of the carbon-based filler is 0.5 parts by mass or less relative to 100 parts by mass of polycarbonate resin (A) even if the carbon-based filler is contained. If the carbon fiber is contained in an amount exceeding the above amount, the dielectric loss tangent tends to be high. For the same reason, the carbon black is preferably not contained, or the content of the carbon black is 0.5 parts by mass or less relative to 100 parts by mass of polycarbonate resin (A) even if the carbon-based filler is contained.

[0037] [Laser direct structuring additive] The polycarbonate resin composition of the present invention preferably does not contain an LDS additive for laser direct structuring (hereinafter also referred to as "LDS"), which allows direct plating or printing on the surface of a molded article. Since the LDS additive is likely to reduce impact resistance, the content is preferably 0 parts by mass or more and less than 0.5 parts by mass per 100 parts by mass of the polycarbonate resin (A). More specifically, it is preferable that the LDS additive is not contained, or if it is contained, the content is 0.5 parts by mass or less per 100 parts by mass of the polycarbonate resin (A).

[0038] An LDS additive is a compound that can form plating or printing when a metal is applied to a laser irradiated surface. When an LDS additive is included, the LDS additive is preferably copper chromium oxide, which preferably contains 10 to 30 mass % copper and 15 to 50 mass % chromium. The copper chromium oxide is preferably an oxide having a spinel structure. Another preferred example of the LDS additive is an oxide containing at least one of antimony and phosphorus and tin, preferably a metal oxide containing antimony and tin, more preferably an oxide in which the tin content is greater than the phosphorus and antimony contents, and further preferably an oxide in which the amount of tin relative to the total amount of tin, phosphorus and antimony is 80 mass% or more. Another preferred example of an LDS additive is a conductor that contains at least two metals and has a resistivity of 5×10 3 It is a conductive oxide with a conductivity of less than Ω·cm.

[0039] [Stabilizer] The polycarbonate resin composition of the present invention preferably contains a stabilizer, and the stabilizer is preferably a phosphorus-based stabilizer or a phenol-based stabilizer.

[0040] Any known phosphorus stabilizer can be used as the phosphorus stabilizer. Specific examples include phosphorus oxoacids such as phosphoric acid, phosphonic acid, phosphorous acid, phosphinic acid, and polyphosphoric acid; metal acid pyrophosphates such as sodium acid pyrophosphate, potassium acid pyrophosphate, and calcium acid pyrophosphate; phosphates of Group 1 or Group 2B metals such as potassium phosphate, sodium phosphate, cesium phosphate, and zinc phosphate; organic phosphate compounds, organic phosphite compounds, and organic phosphonite compounds, with organic phosphite compounds being particularly preferred.

[0041] Examples of organic phosphite compounds include triphenyl phosphite, tris(mononylphenyl)phosphite, tris(mononyl / dinonyl phenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, monooctyl diphenyl phosphite, dioctyl monophenyl phosphite, monodecyl diphenyl phosphite, didecyl monophenyl phosphite, tridecyl phosphite, trilauryl phosphite, tristearyl phosphite, and 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite. Specific examples of such organic phosphite compounds include "ADK STAB 1178", "ADK STAB 2112", and "ADK STAB HP-10" manufactured by ADEKA CORPORATION, "JP-351", "JP-360", and "JP-3CP" manufactured by Johoku Chemical Industry Co., Ltd., and "IRGAFOS 168" manufactured by BASF. The phosphorus-based stabilizer may be contained either as one type or as two or more types in any combination and ratio.

[0042] The content of the phosphorus-based stabilizer is preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, and usually 1 part by mass or less, preferably 0.7 parts by mass or less, more preferably 0.5 parts by mass or less, based on 100 parts by mass of the polycarbonate resin (A). If the content of the phosphorus-based stabilizer is less than the lower limit of the above range, the thermal stabilization effect may be insufficient, and if the content of the phosphorus-based stabilizer is more than the upper limit of the above range, the effect may plateau and become uneconomical.

[0043] The phenol-based stabilizer includes, for example, a hindered phenol-based antioxidant. Specific examples thereof include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], 2,4-dimethyl-6-(1-methylpentadecyl)phenol, diethyl[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphonate, 3,3',3",5,5',5"-hexa-tert-butyl-a,a',a"-(mesitylene-2,4,6- triyl)tri-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, ethylene bis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamino)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, and the like.

[0044] Among them, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate are preferred.Specific examples of such phenol-based antioxidants include "Irganox 1010" and "Irganox 1076" manufactured by BASF, and "Adeka STAB AO-50" and "Adeka STAB AO-60" manufactured by ADEKA. The phenol-based stabilizer may be contained either as one type or as two or more types in any combination and ratio.

[0045] The content of the phenol-based stabilizer is preferably 0.01 parts by mass or more, and usually 1 part by mass or less, preferably 0.5 parts by mass or less, based on 100 parts by mass of the polycarbonate resin (A). By making the content of the phenol-based stabilizer equal to or more than the lower limit of the above range, the effect as a phenol-based stabilizer can be sufficiently obtained. In addition, if the content of the phenol-based stabilizer exceeds the upper limit of the above range, the amount of gas generated tends to increase, which may cause concerns about mold corrosion. By making the content equal to or less than the upper limit, the effect does not plateau and is economical.

[0046] [Release agent] The resin composition of the present invention preferably contains a release agent. Examples of the release agent include aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, and polysiloxane-based silicone oils.

[0047] Examples of the aliphatic carboxylic acid include saturated or unsaturated aliphatic mono-, di- or tri-carboxylic acids. Here, the aliphatic carboxylic acid also includes alicyclic carboxylic acids. Among these, preferred aliphatic carboxylic acids are mono- or di-carboxylic acids having 6 to 36 carbon atoms, and more preferred are saturated aliphatic mono-carboxylic acids having 6 to 36 carbon atoms. Specific examples of such aliphatic carboxylic acids include palmitic acid, stearic acid, caproic acid, capric acid, lauric acid, arachic acid, behenic acid, lignoceric acid, cerotic acid, melissic acid, tetralinic acid, montanic acid, adipic acid, and azelaic acid.

[0048] The aliphatic carboxylic acid in the ester of aliphatic carboxylic acid and alcohol can be, for example, the same as the aliphatic carboxylic acid. On the other hand, the alcohol can be, for example, a saturated or unsaturated monohydric or polyhydric alcohol. These alcohols may have a substituent such as a fluorine atom or an aryl group. Among these, a monohydric or polyhydric saturated alcohol having 30 or less carbon atoms is preferred, and an aliphatic saturated monohydric alcohol or an aliphatic saturated polyhydric alcohol having 30 or less carbon atoms is more preferred. Here, the term aliphatic is used to include alicyclic compounds.

[0049] Specific examples of such alcohols include octanol, decanol, dodecanol, stearyl alcohol, behenyl alcohol, ethylene glycol, diethylene glycol, glycerin, pentaerythritol, 2,2-dihydroxyperfluoropropanol, neopentylene glycol, ditrimethylolpropane, and dipentaerythritol.

[0050] The above ester may contain an aliphatic carboxylic acid and / or alcohol as an impurity. The above ester may be a pure substance, or may be a mixture of a plurality of compounds. The aliphatic carboxylic acid and alcohol that are combined to form an ester may each be used alone or in any combination and ratio of two or more.

[0051] Specific examples of esters of aliphatic carboxylic acids and alcohols include beeswax (a mixture mainly composed of myricyl palmitate), stearyl stearate, behenyl behenate, stearyl behenate, glycerin monopalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, pentaerythritol monopalmitate, pentaerythritol monostearate, pentaerythritol distearate, pentaerythritol tristearate, and pentaerythritol tetrastearate.

[0052] Examples of aliphatic hydrocarbons having a number average molecular weight of 200 to 15,000 include liquid paraffin, paraffin wax, microwax, polyethylene wax, Fischer-Tropsch wax, and α-olefin oligomers having 3 to 12 carbon atoms. The aliphatic hydrocarbons also include alicyclic hydrocarbons. These hydrocarbons may be partially oxidized. Among these, paraffin wax, polyethylene wax, or a partial oxide of polyethylene wax is preferred, and paraffin wax and polyethylene wax are more preferred. The number average molecular weight of the aliphatic hydrocarbon is preferably 5,000 or less. The aliphatic hydrocarbon may be a single substance, but a mixture of substances having various constituent components and molecular weights can also be used as long as the main component is within the above range.

[0053] Examples of polysiloxane-based silicone oils include dimethyl silicone oil, methylphenyl silicone oil, diphenyl silicone oil, and fluorinated alkyl silicone.

[0054] The above-mentioned release agents may be contained alone or in any combination and ratio of two or more kinds.

[0055] The content of the release agent is usually 0.001 parts by mass or more, preferably 0.01 parts by mass or more, and usually 2 parts by mass or less, preferably 1 part by mass or less, and more preferably 0.5 parts by mass or less, based on 100 parts by mass of the polycarbonate resin (A). If the content of the release agent is less than the lower limit of the above range, the effect of releasability may be insufficient, and if the content of the release agent is more than the upper limit of the above range, there is a possibility that a decrease in hydrolysis resistance and mold contamination during injection molding may occur.

[0056] [Additives, etc.] The polycarbonate resin composition of the present invention may contain additives other than those described above, such as ultraviolet absorbers, fluorescent whitening agents, pigments, dyes, flame retardants, impact modifiers, plasticizers, compatibilizers, etc. These additives may be contained in one or more types. A filler, particularly a fibrous filler, may be contained, but the content when contained is preferably less than 5 parts by mass per 100 parts by mass of the polycarbonate resin (A).

[0057] In addition, other resins than the polycarbonate resin (A) may be contained. Examples of other resins include thermoplastic polyester resins such as polyethylene terephthalate, polytrimethylene terephthalate, and polybutylene terephthalate; styrene-based resins such as polystyrene resin, high impact polystyrene resin (HIPS), and acrylonitrile-styrene copolymer (AS resin); polyolefin resins such as polyethylene resin and polypropylene resin; polyamide resin; polyimide resin; polyetherimide resin; polyurethane resin; polyphenylene ether resin; polyphenylene sulfide resin; polysulfone resin; polymethacrylate resin, etc. As other resins, ABS resin and polybutylene terephthalate resin are particularly preferable. When other resins are contained, the amount is preferably 30 parts by mass or less per 100 parts by mass of the polycarbonate resin (A), and more preferably 20 parts by mass or less, 15 parts by mass or less, 10 parts by mass or less, 7 parts by mass or less, 5 parts by mass or less, 3 parts by mass or less, and particularly preferably 1 part by mass or less.

[0058] [Polycarbonate resin composition] The polycarbonate resin composition of the present invention has a high dielectric constant, that is, a dielectric constant at a frequency of 5.8 GHz is 4.5 or more, preferably 5 or more and less than 6.5. The dielectric loss tangent is preferably 0.015 or less. On the other hand, the polycarbonate resin composition of the present invention tends to have a low thermal conductivity, and the thermal conductivity in the resin flow direction (MD direction) during molding of the molded article is preferably 0.7 w / m·k or less. The specific methods for measuring the relative dielectric constant and the dielectric loss tangent are as described in the Examples. The thermal conductivity of the polycarbonate resin composition of the present invention can be measured, for example, by measuring the thermal conductivity (unit: W / m K) in the resin flow direction (MD direction) during molding of a test specimen using a hot disk method thermal property measuring device (for example, "TPS-2500S" manufactured by Kyoto Electronics Manufacturing Co., Ltd.) in accordance with ISO22007-2. The thermal conductivity of the polycarbonate resin composition of the present invention is low, preferably 0.7 w / m·k or less.

[0059] [Method for producing polycarbonate resin composition] There is no limitation on the method for producing the thermally conductive polycarbonate resin composition of the present invention, and a wide variety of known methods for producing polycarbonate resin compositions can be adopted. Examples of such methods include a method in which the above-mentioned essential components and other components that are blended as necessary are premixed using various mixers such as a tumbler or a Henschel mixer, and then melt-kneaded using a mixer such as a Banbury mixer, a roll, a Brabender, a single-screw kneading extruder, a twin-screw kneading extruder, or a kneader. The melt-kneading temperature is not particularly limited, but is usually in the range of 240 to 320°C.

[0060] [Molded products] The above-mentioned polycarbonate resin composition is pelletized and molded into a molded product by various molding methods. It is also possible to directly mold a resin melt-kneaded in an extruder into a molded product without going through the pelletizing process. The shape of the molded article is not particularly limited and can be appropriately selected depending on the use and purpose of the molded article. Examples include plate-like, plate-like, rod-like, sheet-like, film-like, cylindrical, annular, circular, elliptical, polygonal, irregularly shaped, hollow, frame-like, box-like, panel-like, etc.

[0061] The method for molding the molded body is not particularly limited, and any conventionally known molding method can be used, such as injection molding, injection compression molding, extrusion molding, profile extrusion, transfer molding, hollow molding, gas-assisted hollow molding, blow molding, extrusion blow molding, IMC (in-mold coating molding), rotational molding, multi-layer molding, two-color molding, insert molding, sandwich molding, foam molding, and pressure molding.

[0062] Since the polycarbonate resin composition of the present invention is a polycarbonate resin material having a high dielectric constant, a low dielectric loss tangent, and good fluidity and impact resistance, the molded product obtained by molding the composition can be used as a high dielectric constant resin part such as a high dielectric constant resin molded product, a high dielectric constant resin film, a high dielectric constant resin sheet, etc., and is useful for various electronic devices. In particular, the composition can be suitably used for parts with improved touch sensitivity in touch switch parts such as touch panels, touch sensors, and in-vehicle display parts, parts for radio wave reflectors that expand the reachable area of ​​millimeter waves, antenna parts, communication device parts, film capacitors, and other high-performance parts that utilize dielectric properties, and high-performance electric and electronic parts that are compatible with a high dielectric constant. EXAMPLES

[0063] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples, and can be modified as desired without departing from the gist of the present invention. The raw material components used in the following Examples and Comparative Examples are as shown in Table 1 below.

[0064] [Table 1]

[0065] (Examples 1 to 3, Comparative Examples 1 to 9) The components shown in Table 1 were blended in the ratios (parts by mass) shown in Table 3 below and mixed in a tumbler for 20 minutes. The mixture was then melt-kneaded in a twin-screw extruder ("TEX30α" manufactured by The Japan Steel Works, Ltd.) at a cylinder temperature of 280°C, and pellets were obtained by strand cutting.

[0066] <Dielectric constant and dielectric loss tangent> The pellets obtained above were dried at 120°C for 5 hours, and then injection molded in an injection molding machine (Nissei Plastic Industrial Co., Ltd., "NEX80") with a cylinder setting temperature of 280°C and a mold temperature of 80°C to obtain test pieces of 100 mm x 100 mm x 2 mm thick. From the flat test piece obtained above, a flat test piece of 100 mm x 1 mm x 2 mm was obtained by cutting, and then the relative dielectric constant and the dielectric loss tangent at a frequency of 5.8 GHz were measured by the perturbation method using a network analyzer manufactured by KEYSIGHT Corporation and a cavity resonator manufactured by Kanto Electronics Application Development Co., Ltd. The polycarbonate resin composition of the present invention has a high relative dielectric constant, and the relative dielectric constant at a frequency of 5.8 GHz is 4.5 or more, preferably 5 or more and less than 6.5. The dielectric loss tangent is preferably 0.015 or less.

[0067] <Charpy impact strength (unit: kJ / m 2 )> The pellets obtained by the above method were dried at 120°C for 5 hours, and then injection molded in an injection molding machine (Shibaura Machine Co., Ltd., "EC75") under the conditions of a cylinder temperature of 280°C, a mold temperature of 80°C, a screw rotation speed of 80 rpm, and an injection speed of 30 mm / s to produce ISO multipurpose test pieces (3 mmt). Using the obtained ISO multipurpose test piece (3 mmt), the unnotched and notched Charpy impact strength (unit: kJ / m) was measured at a temperature of 23°C based on ISO standard 179-1. 2 ) was measured. The polycarbonate resin composition of the present invention preferably has an unnotched Charpy impact strength of 200 kJ / m 2 and the notched Charpy impact strength is preferably 5 kJ / m 2 More preferably, 6 kJ / m 2 It is.

[0068] <Nominal tensile strain at break (unit:%)> The pellets obtained by the above method were dried at 120°C for 5 hours, and then injection molded in an injection molding machine (Shibaura Machine Co., Ltd., "EC75") under the conditions of a cylinder temperature of 280°C, a mold temperature of 80°C, a screw rotation speed of 80 rpm, and an injection speed of 30 mm / s to produce ISO multipurpose test pieces (4 mmt). Using the obtained ISO multipurpose test piece (thickness 4 mmt), the nominal tensile strain at break (unit: %) was measured in accordance with the ISO527 standard.

[0069] <Overall rating> Based on the above results, the electrical properties and mechanical properties were evaluated comprehensively according to the criteria A, B, and C shown in Table 2 below. [Table 2]

[0070] The results are shown in Table 3 below.

[0071] [Table 3] [Industrial Applicability]

[0072] INDUSTRIAL APPLICABILITY The polycarbonate resin composition of the present invention has a high dielectric constant, a low dielectric tangent, and excellent fluidity (moldability) and impact resistance, and can therefore be suitably used for various molded products.

Claims

1. A polycarbonate resin composition comprising: 100 parts by mass of a polycarbonate resin (A); 3.0 to 6.0 parts by mass of graphite (B) having an aspect ratio of more than 20 and a particle size of 300 μm or less; and a relative dielectric constant at a frequency of 5.8 GHz of 4.5 or more and less than 6.

5.

2. 2. The polycarbonate resin composition according to claim 1, wherein a molded article of the resin composition has a thermal conductivity in the resin flow direction (MD) of 0.7 W / m·K or less.

3. 3. The polycarbonate resin composition according to claim 1, wherein the content of the carbon fiber is 0 to 0.5 parts by mass per 100 parts by mass of the polycarbonate resin (A).

4. 3. The polycarbonate resin composition according to claim 1, wherein the content of the laser direct structuring additive is 0 part by mass or more and less than 0.5 part by mass per 100 parts by mass of the polycarbonate resin (A).

5. A molded article formed from the polycarbonate resin composition according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Polycarbonate resin composition

    JP2021066831A